Pengembangan Sistem Pendidikan Islam dalam Konteks Pelaksanaan Syari'at Islam di Aceh - M. Nasir Budiman (Universitas Islam Negeri Ar-Raniry, 2001)
In their history, Muslim people proved themselves to have reached the highest degree of development in the word. Yet, this is not the case anymore. Muslim people all over the world, including the Acehnese, are in backwardness in many aspects of life, such as in science, technology, economy, politics, and education. Islamic education is seen to play its significant role in solving the problem, especially in Aceh region, where Islamic shari’ah is officially being applied. In this case, there are four new paradigms to be developed in Islamic education, there are al-tahwid, al’dl, al-hurriyyah, and al-mas’uliyyah. It is hoped that these paradigms are capable of solving both the Acehnese and the Muslim problems all over the world.